Associations Between Posterior Communicating Artery Aneurysms and Morphological Characteristics of Surrounding Arteries - Hao, Weili; Hao, Hong; Ren, Chun-Feng; Wang, Xiangling; Gao, Bulang (Frontiers in Neurology, 2022)
Objectives To explore the associations between posterior communicating artery (PComA) aneurysms and morphological characteristics of arteries upstream of and around the PComA bifurcation site. Methods In this study, fifty-seven patients with PComA aneurysms and sixty-two control subjects without aneurysms were enrolled. The centerlines of the internal carotid artery (ICA) and important branches were generated for the measurement and analysis of morphological parameters, such as carotid siphon types, diameters of two fitting circles, and the angle formed by them (D1, D2, and ϕ), length (L) and tortuosity (TL) of ICA segment between an ophthalmic artery and PComA bifurcations, bifurcation angle (θ), tortuosity (TICA and TPComA), and flow direction changes (θICA and θPComA) around the PComA bifurcation site. Results No significant difference (p > 0.05) was found in the siphon types (p = 0.467) or L (p = 0.114). Significant differences (p < 0.05) were detected in D1 (p = 0.036), TL (p < 0.001), D2 (p = 0.004), ϕ (p = 0.008), θ (p = 0.001), TICA (p < 0.001), TPComA (p = 0.012), θICA (p < 0.001), and θPComA (p < 0.001) between the two groups. TICA had the largest area under the curve (AUC) (0.843) in the receiver operating characteristic (ROC) analysis in diagnosing the probability of PComA aneurysms presence and was identified as the only potent morphological parameter (OR = 11.909) associated with PComA aneurysms presence. Conclusions The high tortuosity of the ICA segment around the PComA bifurcation is associated with PComA aneurysm presence.